Edge-coherent oscillation providing nearly continuous transport during edge-localized mode mitigation by n = 1 resonant magnetic perturbation in HL-2A. (15th February 2021) - Sun, T.F.; Liu, Y.; Ji, X.Q.; Liu, Y.Q.; Ke, R.; Gao, J.M.; Wu, N.; Deng, W.; Xu, M.; Duan, X.R.
Abstract: An edge-coherent oscillation (ECO) with a bursting feature was observed in the steep-gradient pedestal region of H-mode plasmas in the HL-2A tokamak, where the type-I edge-localized modes (ELMs) were mitigated by application of n = 1 ( n is the toroidal mode number) resonant magnetic perturbation (RMP). Utilizing a newly developed beam emission spectroscopy (BES) system, it was found that the ECO with a frequency of about 2 kHz is located at the edge pedestal region, and is excited by three-wave interaction of turbulence enhanced by the RMP field through the change of electron density gradient in the pedestal region because of the pump-out effect. The oscillation drives a significant outflow of particles as directly measured by probes, thus providing a channel for nearly continuous extra particle transport across the pedestal during ELM mitigation by RMP.